2015
DOI: 10.1177/1744259115591993
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of two envelope systems: Measurements in non air-conditioned outdoor test cells and simulations

Abstract: Measurements obtained from two non-air-conditioned outdoor full-scale test cells during a year in Torreón, Coahuila, Mexico, are used to compare the thermal performance of two envelope constructive systems for walls and roofs of monolithic concrete buildings. The two constructive systems have the same thickness, one is mono-layered and other is two-layered. The two-layered constructive system has a better thermal performance due to its larger thermal resistances and thermal capacity, and the more-layers effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Furthermore, thermal acceptability was rated at 68% during the cool season and only 33% during the warm season. These results may suggest that these houses are more suitable for the cool season; however the divergence from the neutral temperature was of a similar magnitude in both seasons (see tables 12,13). It may be concluded therefore that people in this region find it easier to cope or adapt to cooler conditions with the aid of warmer clothing during the day and the use of thick blankets at night, but find it more difficult to adapt to warmer conditions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Furthermore, thermal acceptability was rated at 68% during the cool season and only 33% during the warm season. These results may suggest that these houses are more suitable for the cool season; however the divergence from the neutral temperature was of a similar magnitude in both seasons (see tables 12,13). It may be concluded therefore that people in this region find it easier to cope or adapt to cooler conditions with the aid of warmer clothing during the day and the use of thick blankets at night, but find it more difficult to adapt to warmer conditions.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have reported positive findings from the use of multi-layer construction strategies for houses in warm climates such as Turkey [12] and Mexico [13]. Findings indicate that when two construction systems with the same thermal resistance and thermal capacity are compared, the system with more layers results in an improved thermal performance, defined as a reduction in the decrement factor or increase in the time lag (see section 3.2.).…”
Section: Building Envelope Performancementioning
confidence: 89%
“…A recent study conducted by Rincón et al [27] in this location used an adobe building of similar size to assess thermal comfort in earthen buildings. Other authors used similar test cells to investigate thermal performance of building in locations such as Mexico [28], France [29] and Switzerland [30]. Their work showed that test cells represent practical and efficient means to gather high quality data for empirical validation.…”
Section: Description Of the Buildingmentioning
confidence: 99%
“…Alonso (2015) for her doctoral thesis used the same test cells from GESLAB to study the energy rehabilitation of facades: Methodological proposal for the evaluation of innovative solutions, based on the diagnosis of social housing built between 1940 and 1980 [14]. Additionally, Rojas et al (2015) used two non-air-conditioned outdoor test cells and simulations to study the thermal performance of two envelope systems in Mexico [15]. in Ireland, studied the behavior of a suspended particle device switchable glazing in an outdoor test cell with heat removal under varying weather conditions.…”
Section: Introductionmentioning
confidence: 99%